PROFESIONALISME GURU PENDIDIKAN AGAMA KRISTEN DI ERA DIGITAL: MENELADANI YESUS SEBAGAI SANG GURU AGUNG - Tapilaha, Sandra Rosiana; Lawalata, Mozes (The Way: Jurnal Teologi dan Kependidikan, 2025)
This article discusses the professionalism of Christian Religious Education teachers in the digital era, focusing on the example of Jesus as the Great Teacher. The background of this research stems from the challenges faced by teachers in integrating technology in religious teaching, as well as the importance of maintaining spiritual and moral values amidst digital advancements. The significance of this paper lies in the attempt to provide guidance for teachers in developing their professionalism, as well as emphasizing the importance of character and integrity in religious education. The research method used in writing this article is a literature study and qualitative analysis, which includes collecting data from various sources, including books, articles, and previous research on the professionalism of Christian Religious Education teachers. The purpose of this research is to explore how the teaching principles of Jesus can be applied in the context of modern Christian Religious Education, as well as to identify strategies that Christian Religious Education teachers can use to improve their professionalism in the digital age. The results show that by imitating Jesus, Christian Religious Education teachers can develop more effective and relevant teaching approaches, which not only prioritize academic knowledge, but also shape students' character. In addition, this study found that the use of technology in teaching can enrich the learning experience, as long as it remains grounded in strong Christian values. Thus, this article makes an important contribution to the professional development of Christian Religious Education teachers in the digital era.